Analysis of personality traits and their influence on the quality of life of postmenopausal women with regard to genetic factors. Issue 1 (December 2016) - Schneider-Matyka, Daria; Jurczak, Anna; Samochowiec, Agnieszka; Karakiewicz, Beata; Szkup, Małgorzata; Grzywacz, Anna; Grochans, Elżbieta
Abstract Background Quality of life can be perceived as a subjective assessment of different aspects of human functioning. Personality is a factor which determines actions taken by individuals and their tendency to perceive reality in a particular way. Therefore, the assumption that personality may influence the QoL assessment seems reasonable. Our purpose was to assess the relationships between personality traits and the presence of the 44-bp VNTR polymorphism in the 5-HTT(SLC 6A4) promoter region and the 30-bp VNTR polymorphism in theMAO -A promoter region. We also wanted to determine the influence of personality on the quality of life of postmenopausal women. Methods The study involved 214 postmenopausal women from northwest Poland. It was conducted using the NEO-FFI and the SF-36 questionnaires. DNA polymorphisms were identified using the polymerase chain reaction (PCR). Results The average age of the women was 56.8 ± 4.08 years. Half of the respondents had completed second-level education, 69.2 % had life partners, and 53.3 % were professionally active. Women with the3/3 genotype were characterized by significantly lower openness to experience than respondents with otherMAO -A genotypes (p < 0.05). There was a significant correlation between the quality of life and the levels of neuroticism and extroversion, as well as between selected quality of life domains and the levels of agreeableness and conscientiousness. Conclusions (1)Women with the3/3 genotype of the 30-bp VNTR polymorphism in theMAO -A promoter region are characterized by lower levels of openness to experience than women with otherMAO -A genotypes in our study (2) Personality traits may contribute to the assessment of the quality of life.